Overwrite in thin film disk recording systems - Lin, Herbert Gang (2011)
Overwrite in thin film rigid disk recording has been studied experimentally using disks with a wide range of magnetic moment and coercivity. Standard f2/f1 overwrite was investigated in detail at various recording currents and different flying heights. A theoretical model was developed using simple analytical approximations that relate demagnetization-field-induced position shift (hard transition shift) to the measured overwrite. The demagnetization fields due to the leading edge transitions were calculated analytically including a good approximation to the gapped head image. The results compare well with experimental measurements. A new overwrite measurement technique using the second harmonic component of a 0.5f1 signal is also described in this work.